Kinetic and Thermodynamic Study of Cationic Dye Removal Using Activated Biochar Synthesized from Prosopis juliflora Waste - Andrés Abuabara; Carlos Diaz-Uribe; William Vallejo; Freider Duran; Edgar Mosquera-Vargas (ChemEngineering, 2025)
In this study, we synthesized an activated biochar using Prosopis juliflora waste as a carbon source. Citric acid (CA) was used as the chemical agent for biochar activation. The removal of methylene blue (MB) using the fabricated biochar was investigated. A response surface methodology (RSM) experimental design was employed to evaluate the effects of synthesis parameters, including the temperature and the CA/biochar mass ratio, on the biochar’s MB removal efficiency. The impact of adsorption parameters, such as the biochar dosage, pH, MB concentration, and ionic strength, was also examined. Kinetic and isothermal adsorption studies were conducted to assess the efficacy of the activated biochar. The kinetic study revealed a maximum adsorption capacity (qe) of 37.6 mg/g and a rate constant of 0.0022 g mg−1 min−1, with the pseudo-second-order model providing the best fit. The isotherm study indicated that the Freundlich model best described the data, with KF = 37.8 mg/g and 1/nf = 0.498. Thermodynamic analysis showed that the MB adsorption onto the biochar was spontaneous (ΔG = −9.14 kJ/mol), endothermic (ΔH = 17.87 kJ/mol), and driven by an entropy increase (ΔS = 89.20 J/mol·K).